Ermida de Santa Marta. (Casal de Cambra, Sintra). - Rocha, Leonor (2010)
During the last decades of the 19th century, the Chapel of Santa Marta (Casal de Cambra, Sintra) was made into a house. Consequently, its original features were altered and the archaeological levels under it were, to a significant extent, destroyed. With the excavations of the Chapel, we attempted to recover the maximum amount of informacion possible about its original construction. This information is being used as a basis for the reconstruction of the Chapel.